L’étude du suivi du regard : un nouvel outil au service du projet de paysage ? - Vincent Bouvier (Projets de Paysage)
Can the study of the eye tracking contribute to the elaboration and the validation of a landscape project ? The assessment of the eye movements aims at registering and analyzing the way the eyes are moving during observation. The first results confirm the high variation between individuals reacting to a similar visual stimulation and the importance of the observer culture. Beyond our control, our eyes are attracted by an important luminous contrast between the background and the present objects and the position they occupy in the landscape. An important morphological structuration such as line of convergence towards a point of horizon would also encourage visual attraction. It is also reinforced by the semantic value of the object : a living being or an object able to move or what can be source of pleasure or danger are recognized uppermost. In an endogenous way, our attention can orient the selection of visual information before action.